Modelagem e Construção de uma ferramenta de autoria para um Sistema Tutorial Inteligente - Costa, Nilson Santos (2002)
One of the difficullties when building an Intelligent Tutoring System (ITS) is the domain model definition. This must be the result of knowledge acquisition from an experts, usually a teacher. This thesis presents the definition, modelling and implementation of an authoring tool. This tool, named authoring, provides cognitive evaluations to organize a knowledge set within an intelligent tutoring system. Through this tool, the knowledge (domain) of an Expert will be available for Mathnet System. This happens due to the edition or creation of an Expert authoring into a specific domain (knowledge). By the measures, it is possible the automation of a good curricular choice to the next phase to be some proposed by the peer, simulating the teacher s experience, in order to minimize the learning process and provide the use of many pedagogical strategies. Thus, the modelling and implementation of the authoring tool acts as a mechanism of creation and test of knowledge (domain).